Analisis Kelayakan Spent Bleaching Earth ( SBE ) Sebagai Filler Dalam Campuran Aspal AC-WC - Deadha, Fatihatul; Abrar, Aidil; Abdillah, Nuryasin (Sekolah Tinggi Teknologi Dumai, 2024)
Road damage sometimes occurs earlier than the service period, many roads are encountered that are not qualified or the quality of asphalt is low. One of the efforts to improve the quality of asphalt is by modifying the mixture in the pavement layer. The purpose of this study was to determine the results of marshall characteristics with the use of spent bleaching earth as a substitute for filler with variations in levels of 0%,50%,55%,60%,75%,100%. The research method used is a laboratory experiment resulting from Marshall testing that has been carried out on the AC-WC layer using Spent Bleaching Earth, the stability value, flow, MQ, VIM, VMA, VFA at each SBE level cannot all meet the six Marshall characteristic values set by Bina Marga. But the SBE content of 50% and using 60/70 penetration asphalt of 6% can meet the Stability value of 867.76 kg, Flow of 4mm, VIM of 5%, VMA of 16.39%, VFA of 65.12% but the MQ value does not reach 220.11 kg / mm.